Trade and Transport Facilitation in South Asia : Systems in Transition, Volume 1. Summary and Main Report - World Bank (Washington, DC, 2014)
Over the past few decades, the World trading system has become increasingly more open. Tariff rates have been reduced and quantitative restrictions (quotas) have been progressively eliminated, e.g. the Multi-Fiber Agreement (MFA). Most countries have adopted more outward-looking economic policies, seeking to increase growth and employment through expanding exports. Such outward looking policies have even been adopted by countries which previously pursued policies based on import substitution as in South Asia. Protective trade restrictions still persist, but tend to be in terms of more subtle non-tariff barriers (such as sanitary or phyto-sanitary standards), though anti-dumping measures and temporary quantity restrictions are still used by many countries to shield domestic producers. Trade regulations no longer solely attempt to protect domestic producers; their scope has extended to cover the need for enhanced security and the desire for greater consumer protection through the traceability of the production chain for many agricultural products. Intense competition compels firms to reduce costs throughout their manufacturing and distribution processes. Outsourcing to lower cost firms and countries has been one major source of cost reduction, reduced inventory costs through just-in-time manufacturing, and distribution systems has been another. Both are predicated on efficient, reliable and low-cost supply chains. With the worldwide fall in tariff levels, the efficiency of supply chains and the associated logistics costs are becoming core determinants of the competitiveness of both firms and countries. They may also influence the destination of inward direct investment; many countries can offer low labor costs and tax incentives, fewer can offer quick, efficient, reliable, and low cost logistics.